Effect of Different Concentrations of Esmolol on Perioperative Hemodynamics and Analgesia in Patients Undergoing Colectomy: A Prospective, Randomized Controlled Study - Song F; Jin Y; Li P; Zheng C; Zhao X (Dove Medical Press, 2021)
Fuxi Song,1 Yanwu Jin,1 Peng Li,1 Chao Zheng,2 Xin Zhao1 1Department of Anesthesiology, The Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of China; 2Department of Breast Surgery, The Second Hospital, School of Medicine, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of ChinaCorrespondence: Xin ZhaoDepartment of Anesthesiology, The Second Hospital, Cheeloo College of Medicine, Shandong University, No. 247 Beiyuan Street, Jinan, Shandong, 250033, People's Republic of ChinaFax +86-531-88962544Email lujnzx@sohu.comPurpose: The aim of this study was to investigate the efficacy of esmolol on intraoperative hemodynamic and perioperative analgesic management.Methods: Totally, 125 patients undergoing colectomy were randomly divided into three groups. Group S (saline group) was administered 0.75 mL/kg/h of normal saline for 5 min before anesthesia induction and maintenance of 0.25 mL/kg/h; Group E1 and Group E2 were administered 0.5 mg/kg and 1.0 mg/kg esmolol for 5 min before anesthesia induction, and maintained of 0.5 mg/kg/h and 2.0 mg/kg/h, respectively. Several parameters including indexes of hemodynamics variation (primary outcome), intra- and postoperative analgesic usage, and pain score were measured.Results: Group E1 and Group E2 had significantly lower intubation response than Group S (P = 0.007, P = 0.001), and extubation response of Group E2 was significantly lower than Group S (P = 0.007). The opioid consumption in Group E1 and Group E2 was significantly lower than in Group S intraoperatively (P = 0.020 and 0.007). The incidence of postoperative adverse reactions among the three groups was not statistically significant (P = 0.368 and 0.772).Conclusion: Esmolol 0.5 mg/kg and 1.0 mg/kg infusion before intubation both can effectively inhibit the intubation response, while only maintenance with 2.0 mg/kg/h of esmolol can reduce the incidence of extubation response. At the same time, esmolol can decrease intraoperative opioid requirement without increasing the risk of adverse reactions.Trial Registration: ChiCTR1900024538 and the date of registration was July 15, 2019 at http://www.chictr.org.cn.Keywords: esmolol, hemodynamics, analgesia, intubation response, extubation response